Influence of intravenous thiamine supplementation on blood lactate concentration prior to cardiac surgery: A double-blinded, randomised controlled pilot study. Issue 8 (August 2015) - Luger, Maria; Hiesmayr, Michael; Köppel, Pamina; Sima, Beatrix; Ranz, Ines; Weiss, Christian; König, Jürgen; Luger, Eva; Kruschitz, Renate; Ludvik, Bernhard; Schindler, Karin
Abstract : BACKGROUND: Stress related to surgery and critical illness depletes thiamine, essential in energy metabolism, and might result in high blood lactate concentrations and higher mortality. OBJECTIVES: We hypothesised that thiamine supplementation would increase blood concentration of thiamine and reduce blood lactate concentration postoperatively. Moreover, we aimed to identify the prevalence of, and risk factors for, high blood lactate concentrations. DESIGN: This was a double-blind, randomised controlled pilot study from February to July 2012 including 30 patients scheduled for cardiac surgery with cardiopulmonary bypass. INTERVENTIONS: Patients were assigned randomly to receive thiamine (300 mg in 0.9% Normal saline solution) or placebo (0.9% Normal saline) preoperatively. MAIN OUTCOME MEASURES: One arterial blood sample was taken preoperatively and another postoperatively to measure thiamine concentration, and multiple samples were taken during surgery and ICU stay to determine lactate concentrations. Twenty-four hour urine samples were collected to measure urinary thiamine concentration. Preoperatively, we assessed extracellular mass to body cell mass ratio (ECM/BCM). RESULTS: The mean (SD) age of the patients was 58 (12) years, 73% were overweight, 10% were malnourished and the prevalence of thiamine deficiency was 10%. Patients in the thiamine group had significantly higher blood thiamine concentrations 2 days postoperatively [805.2 ± 289.8 ng g -1 haemoglobin (Hb)] than those in the placebo group (591.2 ± 100.7 ng g -1 Hb, P < 0.01). The mean blood lactate concentration changed significantly over time, but did not differ significantly between the groups. Patients with ECM/BCM more than 1 had higher lactate concentrations on admission to ICU than those with ECM/BCM less than 1 (2.1 ± 0.7 vs. 1.7 ± 0.6, P = 0.09) and were at a significantly greater risk of having a higher lactate concentration on ICU admission [odds ratio (OR) 13.5, 95% confidence interval (95% CI) 1.0 to 179.4, P < 0.05]. On the basis of these results, a sample size calculation for a larger study has been facilitated. CONCLUSION: Thiamine supplementation caused normalisation of blood and urine concentrations postoperatively but without a significant reduction in lactate concentration or clinical outcome. Body composition played an important role in lactate formation. Further research focusing on preoperative screening and optimal treatment of high lactate concentrations in this specific population is warranted. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT01524315.